Recent Advances in Costimulatory Blockade to Induce Immune Tolerance in Liver Transplantation - Ding, Mingjie; He, Yuting; Zhang, Shuijun; Guo, Wenzhi (Frontiers in Immunology, 2021)
Liver transplantation is an effective way to treat end-stage liver disease. Postoperative patients generally need to take immunosuppressive drugs to prevent the occurrence of rejection. However, some transplant recipients do not show rejection after removal of immunosuppressive agents and their liver function is normal. This phenomenon is called immune tolerance and is the ultimate goal of clinical transplant physicians. Co-stimulatory molecules play an important role in maintaining T-cell tolerance and T-cell-mediated immune responses. The blocking of costimulatory molecular pathway can change the immune response of T cells and prolong the survival time of grafts. With the increasing understanding of the role of costimulatory molecules, blocking costimulatory molecular pathways has been effectively used to induce immune tolerance in animal transplantation models. This article mainly reviews the current aspects of blocking co-stimulatory molecular pathways in inducing immune tolerance in liver transplantation and prospects for its clinical application.